Lived experience of cognitive-communication changes for people with acquired brain injury and familiar communication partners: A qualitative evidence synthesis - Nicholas Behn; Iben Christensen; Madeline Cruice; Katerina Hilari; Ian Kellar; Leanne Togher (PLoS ONE, 2026)
Background and objectives Cognitive-communication disorder (CCD) is common after acquired brain injury (ABI), reported in about two-thirds of people who sustain an injury. Quantitative studies have found that the disorder can negatively impact a person’s ability to socially re-integrate into the community, return to work or education and achieve a good quality of life. However, little is known about how the disorder impacts people with ABI and the family. Therefore, the aim of this qualitative evidence synthesis was to provide a detailed exploration of the lived experience of CCD for people with ABI and their family members. Methods A systematic literature search was conducted across eight databases (CINAHL Ultimate, PsycINFO, PsycARTICLES, Medline, EMBASE, AMED, Scopus, PubMed) to August 2025. Studies were included if they reported on people with ABI who present with CCD (or similar term) and/or familiar communication partners whereby the impact of the disorder was described. Relevant data were extracted, and studies were critically appraised using the Critical Appraisal Skills Programme (CASP) qualitative checklist and the confidence of the findings was assessed using GRADE-CERQual tool. The final included studies were synthesised using thematic analysis. Results 13 articles met the eligibility criteria and reported on 103 people with ABI with CCD and 66 familiar communication partners including spouses, parents, friends, carers, siblings and children. Methodologies comprised interviews (n = 10), focus groups (n = 1), spoken discourse samples (n = 1) and online survey (n = 1). Eight main analytic themes were identified centred around the experiences of both people with ABI: (1) communicating is not easy; (2) lack of awareness and feeling tired; (3) anxiety, embarrassment and isolation; (4) connecting with others; and (5) participation and identity; and their familiar communication partner: (6) adjusting to giving increased support; (7) emotional toll of supporting; (8) relationship and life role changes. Conclusions This review highlights the broad and unique impacts of CCD for both people with ABI and their familiar communication partners. People with ABI require tolerance to manage their communication difficulties; and communication partners require education, support and training to manage the change in relationship. These findings underpin the need for interventions to include partners in rehabilitation and for therapists to consider the diverse needs of people with ABI including emotions, relationships, social participation and changes to identity.